ANALISIS PENGARUH TINGKAT PENDIDIKAN, UPAH, USIA, PENGALAMAN KERJA DAN JAM KERJA TERHADAP PRODUKTIVITAS TENAGA KERJA PADA INDUSTRI MANUFAKTUR (Studi Kasus Bagian Produksi PT. Waskita Beton Precast Plant Sidoarjo) - Attaqi, Lifya Fillahi (Journal of Development Economic and Social Studies, 2022)
This study aims to determine the effect of education level, wages, age, workexperience, and working hours on labor productivity in the production division of PT.Waskita Beton Precast Plant Sidoarjo. This research is descriptive quantitative research withdata collection methods through questionnaires distributed to all workers in the productionsection of PT. Waskita Beton Precast Plant Sidoarjo with a sample of 91 workers. Thecollected data were processed and tested through the classical assumption test (normality test,multicollinearity test, heteroscedasticity test, autocorrelation test, linearity test) andhypothesis testing with multiple regression analysis, partial statistical test, simultaneousstatistical test, and the coefficient of determination. The test in this research used a statisticalanalysis computer program, SPSS version 22. The results showed that the education level(X1) partially have a negative and insignificant effect on labor productivity (Y), wage (X2);age (X3); work experience (X4) and working hours (X5) partially have a positive andsignificant effect on labor productivity (Y). From the results of simultaneous statisticaltesting, it was found that the education level (X1), wages (X2), age (X3), work experience(X4) and working hours (X5) simultaneously have a significant effect on labor productivity(Y) by 63.2% while the remaining 36.8% is affected by other variables outside the modeladopted in this study. Keywords: Education Level, Wages, Age, Work Experience, Hours of Work, LaborProductivity